PENGGUNAAN ABU KERTAS KARTON SEBAGAI PENGGANTI FILLER PADA CAMPURAN ASPAL - Isfak Ibnu Ahmad; Rizkiardi, Aditya; Hartatik, Nurani; Gondoarum, Siti Sekar; Punarta, I Gede Agus (Jurnal Teknik Sipil dan Arsitektur, 2025)
The ever-increasing waste of paperboard is a serious challenge to the environment, prompting this research to explore the potential of paperboard ash as a filler replacement in asphalt mixtures. This research was conducted at the Laboratory of the National Road Implementation Center of East Java-Bali, with testing methods that included sieve analysis, specific gravity measurement, and X-Ray Fluorescence (XRF) analysis. The test results showed that 82.03% of the paper ash particles successfully passed the No. 200 sieve, indicating that this material is fine enough to function as a filler in asphalt mixtures. In addition, the average specific gravity obtained was 2.628, which meets the provisions in the 2018 Bina Marga General Specifications (Revision 2). XRF analysis revealed a dominant composition of calcium oxide (CaO) of 72.20%, followed by silica (SiO2) 10.9% and alumina (Al2O3) 6.8%, showing similarities with limestone filler. These findings indicate that paperboard ash can not only improve the stability of asphalt mixtures, but also contribute to waste management. By utilizing waste paperboard as filler, this research plays a role in sustainable development efforts and reduces negative impacts on the environment. In addition, the use of paperboard ash as an alternative filler in asphalt mixtures can also help reduce dependence on non-renewable natural resources, as well as reduce the volume of waste that ends up in landfills. Therefore, the use of paperboard ash as an alternative filler in asphalt mixtures is worth considering in modern construction practices. Keyword: paperboaard ash, alternative filler, asphalt